2007
DOI: 10.1007/s10856-007-0145-y
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of adsorbed silane on fillers used in dental composite restoratives and its effect on composite properties

Abstract: The purpose was to study the effect of silane treatment of fillers on viscosity, flexural strength, and hydrolytic degradation of experimental dental composite resins fabricated with these fillers. The fillers consisted of a mixture of barium glass and amorphous silica. The resin was mainly based on ethoxylated bisphenol A dimethacrylate and polycarbonate dimethacrylate. The adsorption of silane on the filler surface was characterized by FTIR. There was significant correlation between the adsorbed silane on fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 10 publications
3
19
0
3
Order By: Relevance
“…This behavior is in agreement with other studies that reported a similar burst effect of polymer-containing drugs 40 due to the drug molecules present on the outer surface of the disks. This behavior is in agreement with other studies that reported a similar burst effect of polymer-containing drugs 40 due to the drug molecules present on the outer surface of the disks.…”
Section: Chx Release From Different Samplessupporting
confidence: 93%
“…This behavior is in agreement with other studies that reported a similar burst effect of polymer-containing drugs 40 due to the drug molecules present on the outer surface of the disks. This behavior is in agreement with other studies that reported a similar burst effect of polymer-containing drugs 40 due to the drug molecules present on the outer surface of the disks.…”
Section: Chx Release From Different Samplessupporting
confidence: 93%
“…The inferior BFS of the 0% silane group was already expected, based on previous studies. 12,14,16 Moreover, the lower resistance of this group to crack propagation was verified by the lower K IC .…”
Section: Discussionmentioning
confidence: 66%
“…12,13,14,15,16,17 The silane interphase is most commonly composed of the 3-MPTS (γ-3-methacryloxypropyltrimethoxysilane) monomer, a bifunctional molecule capable of both polymerizing with the organic resin matrix and establishing a covalent oxane bond (Si-O-Si) with the surface of the filler particles. 13,17,18 Many studies have researched the influence of the silane interphase on the properties of resin composites; 12,13,14,15,16 however, the data reported in the literature are very controversial, with some studies indicating no significant differences in the various static mechanical properties 14,15,18 Declaration of Interests: The authors certify that they have no commercial or associative interest that represents a conflict of interest in connection with the manuscript. or in the hydrolytic stability 18 of composites with a wide range of silane concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Crack growth along the matrix/particle interface is a dominant fracture mechanism for this kind of composites (Chan et al , 2007). The low flexural strength is caused by the poor adhesion between ceramic and polymer phase, which can be improved by surface treatment, called silanization (Karmaker et al , 2007). As a result, the observations of the nano‐structure carried out here suggest an efficient way of improving the mechanical properties of composites containing this type of filler – silanization with a higher content of silane.…”
Section: Resultsmentioning
confidence: 99%